Effect Of Stretchable Conductive Ink (SCI) On Electrical Conductivity Under Tensile Stress - Masripan, Nor Azmmi; Salim, Mohd Azli; Lin, Soong Jin; Mansor, Muhd Ridzuan; Akop, Mohd Zaid; Abdul Hamid, Nurfaizey; Wasbari, Faizil; Noordin, Aminurrashid (Penerbit UniMAP, 2021)
Conductive ink is widely used in various fields, especially in the electronic printed industry. Conductive ink is more flexible, smaller, and possesses multi-purpose functions as compared to traditional wire and electronic devices. This research aims to investigate the resistivity of the conductive ink under tensile stress. The carbon conductive ink was printed on the thermoplastic polyurethane (TPU) and cured in the oven at 120 °C for 30 minutes. The conductive ink was clamped on the stretching equipment and stretched at different elongation values. The resistivity was measured by a multi-meter and the sheet resistance was measured by a four-point probe. For the 40 mm length of conductive ink, the initial resistance was 0.562 kΩ and became 1.217 kΩ when it was stretched up to 18 %of its initial length. The sheet resistance of the conductive ink was also increasing due to the defect on the surface of conductive ink under the tensile stress. For the 40 mm length of conductive ink, the sheet resistance was 793.17 R/sq at the initial state and became 3059.37 R/sq when it was stretched until 18 % of its initial length. By comparing the different lengths of the conductive ink, the cracking point for 40 mm length of conductive ink can be observed at the 5.6mm of elongation with the strain level is 0.14. The cracking point of 60mm length of conductive ink was 9.6mm of elongation with 0.16 of the strain levels. The strain level of the cracking point between the different lengths of conductive ink was very closed. In conclusion, under the tensile stress, the sheet resistance and resistivity are increasing, which means the drop in conductivity. The conductive ink started to crack when the strain level reached around 0.15.